Repairable ultraviolet curing adhesive, and preparation method and repair method thereof
By using polyurethane acrylate oligomers with different wavelengths of ultraviolet light irradiation mechanisms in photocuring glue, the self-healing of colloids is achieved, the bond failure problem caused by microcracks of photocuring glue is solved, and the safety and stability are improved and the use is improved. life.
Patent Information
- Application Number
- CN202411507738.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-28
- Publication Date
- 2024-12-20
AI Technical Summary
Photocuring glue is prone to microcracks during use and aging, resulting in bond failure. It is difficult for traditional repair methods to effectively repair internal microcracks, which poses safety hazards and affects service life and stability.
Develop a reworkable ultraviolet curable adhesive that can achieve self-healing by ultraviolet irradiation at different wavelengths, including acrylate monomers, polyurethane acrylate oligomers A and B, photoinitiators and fillers, polyurethane acrylate oligomers A is cross-linked under 350nm ultraviolet light and de-crosslinked at 254nm. The bonding performance is enhanced by heating or high-frequency vibration to achieve self-healing and repair of colloids.
It realizes self-repair of colloids, reduces the difficulty of repair, extends service life, improves safety and stability, simplifies operations, and reduces resource consumption and environmental pollution.
Smart Images

Figure BDA0005104499000000031 
Figure BDA0005104499000000041 
Figure BDA0005104499000000081
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of photocuring adhesives, and in particular relates to a reworkable ultraviolet light curing adhesive and a preparation method and a rework method thereof. Background Art
[0002] During the use and aging process, light-curing glue will inevitably produce microcracks and unpredictable damage due to external forces or environmental induction. Among them, internal microcracks are the easiest to produce and are generally not detectable by the naked eye. They must rely on precise detection instruments. Once internal microcracks are generated, they will continue to expand and converge. When they converge to a certain extent, they will cause internal stratification or macroscopic damage to the glue, which will pose certain safety hazards, thus making the light-curing glue bond ineffective and affecting its service life and safety stability.
[0003] Traditional repair methods require manual repair of visible damaged areas using light-curing glue or welding. For sealed internal cracks, components need to be disassembled and repaired, which is difficult and has poor results.
[0004] Therefore, it is necessary to develop an intrinsically repairable and reworkable UV-curable adhesive to extend the service life and improve safety and stability. Summary of the invention
[0005] In view of the shortcomings of the prior art, the present invention aims to provide a repairable UV curing adhesive and a preparation method thereof. The repairable UV curing adhesive can achieve self-repair through UV light irradiation of different wavelengths, thereby achieving repair, with simple operation and low repair difficulty.
[0006] To achieve this object, the present invention adopts the following technical solutions:
[0007] In a first aspect, the present invention provides a reworkable UV-curable adhesive, wherein the reworkable UV-curable adhesive comprises the following components: an acrylate monomer, a polyurethane acrylate oligomer A, a polyurethane acrylate oligomer B, a photoinitiator, and a filler.
[0008] The raw materials for preparing the polyurethane acrylate oligomer A include 5,7-dihydroxy-4-methylcoumarin, halogen-substituted monoalkyl alcohol, isooctyl acrylate, isophorone diisocyanate (IPDI) and a hydroxyl-containing acrylate compound.
[0009] In the present invention, the raw materials for preparing the polyurethane acrylate oligomer A include 5,7-dihydroxy-4-methylcoumarin, so that it has the characteristics of coumarin and coumarin derivatives that can react under ultraviolet light of different wavelengths, can undergo a "2+2" cycloaddition reaction under 350nm ultraviolet light, and can decrosslink under 254nm ultraviolet light.
[0010] In the present invention, the repairable UV-curable adhesive prepared by compounding the polyurethane acrylate oligomer A with an acrylate monomer, a polyurethane acrylate oligomer B and a photoinitiator undergoes cross-linking after being irradiated with 350nm ultraviolet light, the colloid becomes hard, and the bonding strength increases, so that materials such as plastics, glass and metals can be well bonded. After long-term use and aging, the cured repairable UV-curable adhesive has microcracks or macro damages. After irradiating the microcracks or macro damages with 254nm ultraviolet light, the cured repairable UV-curable adhesive will be partially de-crosslinked, so that the strength of the colloid itself decreases and the colloid becomes soft. Then, the microcracks or macro damages are healed in an energy-enhanced manner by heating or high-frequency vibration, and then the adhesive can be restored to its initial strength after being irradiated with 350nm ultraviolet light. In addition, after irradiating the microcracks or macro damages with 254nm ultraviolet light, the strength of the colloid itself decreases and the colloid becomes soft, so that the adherends can be conveniently disassembled, repaired and re-bonded. The repairable UV-curable adhesive is irradiated with UV lights of different wavelengths in sequence so that micro cracks or macro damage caused by aging can be eliminated, the bonding performance of the repairable UV-curable adhesive can be restored, and self-repair can be achieved, thereby achieving repair, simple operation, and low difficulty of repair, which helps to increase the service life of the repairable UV-curable adhesive and improve safety and stability, save resources, and reduce environmental pollution.
[0011] Preferably, the acrylic ester monomer includes any one or a combination of at least two of isobornyl acrylate, N,N-dimethylacrylamide, hydroxyethyl methacrylate, tetrahydrofuran acrylate, tetrahydrofuran methacrylate, ethoxylated tetrahydrofuran acrylate, trimethylolcyclohexyl acrylate, acetone glycerol acrylate or cyclotrimethylolpropane formal acrylate.
[0012] Preferably, the halogen-substituted monohydric alkyl alcohol comprises chlorine-substituted monohydric alkyl alcohol and / or bromine-substituted monohydric alkyl alcohol.
[0013] Preferably, the halogen-substituted monohydric alkyl alcohol comprises 4-bromo-1-butanol and / or 2-bromoethanol.
[0014] Preferably, the hydroxyl-containing acrylate compound includes any one or a combination of at least two of hydroxyethyl acrylate (HEA), hydroxyethyl methacrylate (HEMA), hydroxypropyl acrylate (HPA), hydroxybutyl acrylate (HBA) or caprolactone acrylate (CA).
[0015] Preferably, the polyurethane acrylate oligomer A is prepared by the following method:
[0016] (1) 5,7-dihydroxy-4-methylcoumarin and a halogen-substituted monoalkyl alcohol are reacted to obtain a compound having a structure as shown in Formula I.
[0017]
[0018] In formula I, R is an alkylene group having 2 to 10 carbon atoms (e.g., 2, 3, 4, 5, 6, 7, 8 or 9).
[0019] (2) The compound having the structure shown in Formula I obtained in step (1) is dissolved in isooctyl acrylate, and then mixed with isophorone diisocyanate, reacted, and a hydroxyl-containing acrylate compound is added for end-capping reaction to obtain the polyurethane acrylate oligomer A.
[0020] In the present invention, the structural unit formed by the compound having the structure shown in Formula I in the polyurethane acrylate oligomer A undergoes crosslinking and decrosslinking reaction under 350nm or 254nm ultraviolet light irradiation as shown in Formula II.
[0021]
[0022] In formula II, ---- represents a connecting bond, and R is an alkylene group having 2 to 10 carbon atoms.
[0023] Preferably, the mass ratio of the 5,7-dihydroxy-4-methylcoumarin and the halogen-substituted monoalkyl alcohol in step (1) is 1:(2-2.5), for example, 1:2.1, 1:2.15, 1:2.2, 1:2.25, 1:2.3, 1:2.35, 1:2.4 or 1:2.45, etc.
[0024] Preferably, the mass ratio of the compound having the structure shown in formula I and isophorone diisocyanate in step (2) is 1:(2-3), for example, 1:2.1, 1:2.2, 1:2.3, 1:2.4, 1:2.5, 1:2.6, 1:2.7, 1:2.8 or 1:2.9, etc.
[0025] Preferably, the mass ratio of the compound having the structure shown in formula I and isooctyl acrylate in step (2) is 1:(0.8-1.2), for example, 1:0.85, 1:0.9, 1:0.95, 1:1, 1:1.05, 1:1 or 1:1.15, etc.
[0026] Preferably, the mass ratio of isophorone diisocyanate to the hydroxyl-containing acrylate compound in step (2) is 1:(0.6-1.9), for example, 1:0.8, 1:1, 1:1.2, 1:1.4, 1:1.6 or 1:1.8, etc.
[0027] Preferably, the reaction temperature in step (1) is 80-90°C (e.g., 81°C, 82°C, 83°C, 84°C, 85°C, 86°C, 87°C, 88°C or 89°C, etc.), and the reaction time is 16-20h (e.g., 16.5h, 17h, 17.5h, 18h, 18.5h, 19h or 19.5h, etc.).
[0028] Preferably, the reaction temperature in step (2) is 20-40°C (e.g., 22°C, 24°C, 26°C, 28°C, 30°C, 32°C, 34°C, 36°C or 38°C, etc.), and the reaction time is 0.5-1h (e.g., 0.55h, 0.6h, 0.65h, 0.7h, 0.75h, 0.8h, 0.85h, 0.9h or 0.95h, etc.).
[0029] Preferably, the temperature of the end-capping reaction in step (2) is 40-60°C (for example, 42°C, 44°C, 46°C, 48°C, 50°C, 52°C, 54°C, 56°C or 58°C, etc.), and the time is 4-6h (for example, 4.2h, 4.4h, 4.6h, 4.8h, 5h, 5.2h, 5.4h, 5.6h or 5.8h, etc.).
[0030] Preferably, the step (1) specifically comprises the following steps: dissolving 5,7-dihydroxy-4-methylcoumarin in a solvent, adding potassium carbonate, adding dropwise a halogen-substituted monoalkyl alcohol, reacting at 80-90°C (e.g., 81°C, 82°C, 83°C, 84°C, 85°C, 86°C, 87°C, 88°C or 89°C, etc.) for 16-20h (e.g., 16.5h, 17h, 17.5h, 18h, 18.5h, 19h or 19.5h, etc.), separating and purifying to obtain a compound having a structure as shown in Formula I-1.
[0031] Preferably, the solvent in step (1) comprises dimethylformamide (DMF).
[0032] Preferably, the mass ratio of the 5,7-dihydroxy-4-methylcoumarin to the solvent in step (1) is 1:(18-22), for example, 1:18.5, 1:19, 1:19.5, 1:20, 1:20.5, 1:21 or 1:21.5, etc.
[0033] Preferably, the mass ratio of 5,7-dihydroxy-4-methylcoumarin to potassium carbonate in step (1) is 1:(7-10), for example: 1:7.5, 1:8, 1:8.5, 1:9 or 1:9.5, etc.
[0034] Preferably, the step (2) specifically comprises the following steps: dissolving the compound having the structure shown in formula I in isooctyl acrylate, mixing with a catalyst and isophorone diisocyanate, reacting at 20-40° C. for 0.5-1 h, adding a hydroxyl-containing acrylate compound and performing a capping reaction at 40-60° C. for 4-6 h to obtain the polyurethane acrylate oligomer A.
[0035] Preferably, the catalyst in step (2) comprises dibutyltin dilaurate.
[0036] Preferably, in step (2), the mass ratio of the compound having the structure shown in formula I to the catalyst is 1:(0.005-0.01).
[0037] The present invention has no particular limitation on the selection of the polyurethane acrylate oligomer B. All polyurethane acrylate oligomers commonly used in photocurable adhesives in the art are applicable, including but not limited to BR-543M from Bomar or CN8888 from Sartomer.
[0038] Preferably, the photoinitiator includes any one or a combination of at least two of 1-hydroxycyclohexyl phenyl ketone, 2,4,6-(trimethylbenzoyl)diphenyl phosphine oxide, 2-methyl-1-(4-methylthiophenyl)-2-morpholinyl-1-propanone, 2-hydroxy-2-methyl-1-phenyl-1-propanone, 2-phenylbenzyl-2-dimethylamine-1-(4-morpholinobenzylphenyl)butanone, methyl benzoylformate, phenylbis(2,4,6-trimethylbenzoyl)phosphine oxide, 2-isopropylthioxanthone, benzoin dimethyl ether, dimethylbenzil ketal or benzophenone, and more preferably a combination of 1-hydroxycyclohexyl phenyl ketone and phenylbis(2,4,6-trimethylbenzoyl)phosphine oxide.
[0039] Preferably, the mass ratio of 1-hydroxycyclohexyl phenyl ketone and phenyl bis(2,4,6-trimethylbenzoyl)phosphine oxide is (2-4):1, for example, 2.2:1, 2.4:1, 2.6:1, 2.8:1, 3:1, 3.2:1, 3.4:1, 3.6:1 or 3.8:1, etc.
[0040] Preferably, the filler comprises hydrophobic fumed silica.
[0041] Preferably, the reworkable UV-curable adhesive comprises the following components by mass percentage: the reworkable UV-curable adhesive comprises the following components by mass percentage: 35% to 48% (e.g., 37%, 39%, 41%, 43%, 45% or 47%) of acrylate monomer, 18% to 35% (e.g., 20%, 22%, 24%, 26%, 28%, 30%, 32% or 34%) of polyurethane acrylate oligomer A, 20% to 35% (for example, 22%, 24%, 26%, 28%, 30%, 32% or 34%, etc.), photoinitiator 2% to 5% (for example, 2.5%, 3%, 3.5%, 4% or 4.5%, etc.) and filler 1% to 4% (for example, 1.3%, 1.6%, 1.9%, 2.2%, 2.5%, 2.8%, 3.1%, 3.4% or 3.7%, etc.).
[0042] In a second aspect, the present invention provides a method for preparing the reworkable UV-curable adhesive as described in the first aspect, the preparation method comprising mixing an acrylate monomer, a polyurethane acrylate oligomer A, a polyurethane acrylate oligomer B, a photoinitiator and a filler to obtain the reworkable UV-curable adhesive.
[0043] Preferably, the mixing specifically includes mixing acrylate monomers, polyurethane acrylate oligomer A, and polyurethane acrylate oligomer B, and then adding a photoinitiator and a filler and stirring and mixing.
[0044] In a third aspect, the present invention provides a method for repairing the repairable UV-curable adhesive as described in the first aspect, the repair method comprising the following steps: irradiating the cured repairable UV-curable adhesive as described in the first aspect with 254nm UV light, healing micro cracks or macro damage by heating or high-frequency vibration, and then irradiating with 350nm UV light to complete the repair.
[0045] Preferably, the 254nm ultraviolet light irradiation time is 100-150s, and the energy is 50000-70000mJ / cm 2 .
[0046] Preferably, the 350nm ultraviolet light irradiation time is 8 to 12 seconds, and the energy is 4000 to 6000mJ / cm 2 .
[0047] Compared with the prior art, the present invention has the following beneficial effects:
[0048] In the present invention, the repairable UV-curable adhesive prepared by compounding polyurethane acrylate oligomer A with acrylate monomers, polyurethane acrylate oligomer B and photoinitiator undergoes cross-linking after 254nm UV irradiation, the colloid becomes hard, the bonding strength increases, and the bonding strength to polycarbonate and acrylonitrile-styrene-butadiene copolymer is ≥4MPa. Preferably, the bonding strength to polycarbonate and acrylonitrile-styrene-butadiene copolymer is ≥7MPa, and the adhesive can be well bonded to materials such as plastics, glass and metals; after 254nm UV irradiation, the cured repairable UV-curable adhesive undergoes partial de-crosslinking, the colloid becomes soft, and the micro cracks or macro damages are healed by heating or high-frequency vibration and the bonding strength decreases after the colloid becomes soft. The adhesive strength of the adhesive is low, the adhesive strength of the adhesive to polycarbonate and acrylonitrile-styrene-butadiene copolymer is ≤3Mpa, preferably, the adhesive strength of the adhesive to polycarbonate and acrylonitrile-styrene-butadiene copolymer is ≤1MPa, and the adherends can be easily separated; after irradiation with 350nm ultraviolet light, curing can be restored to a level close to the initial adhesive strength, the adhesive strength of the adhesive to polycarbonate and acrylonitrile-styrene-butadiene copolymer is ≥2MPa, preferably, the adhesive strength of the adhesive to polycarbonate and acrylonitrile-styrene-butadiene copolymer is ≥5.5MPa, so that rework can be achieved, the operation is simple, the rework difficulty is low, and it is helpful to increase the service life of the reworkable UV curing adhesive and improve safety and stability, save resources, and reduce environmental pollution. DETAILED DESCRIPTION
[0049] The technical solution of the present invention is further described below by specific implementation methods. It should be understood by those skilled in the art that the embodiments are only to help understand the present invention and should not be regarded as specific limitations of the present invention.
[0050] Preparation Example 1
[0051] This preparation example provides a polyurethane acrylate oligomer A, specifically a polyurethane acrylate oligomer A-1, and the polyurethane acrylate oligomer A-1 is prepared by the following method:
[0052] (1) Dissolve 1 part by weight of 5,7-dihydroxy-4-methylcoumarin in 20 parts by weight of dimethylformamide, add 9 parts by weight of potassium carbonate, dropwise add 2.5 parts by weight of 4-bromo-1-butanol, react at 80° C. for 20 hours, separate and purify to obtain a compound having a structure as shown in Formula I-1;
[0053]
[0054] (2) Dissolve 1 part by weight of the compound having the structure shown in Formula I-1 obtained in step (1) in 1 part by weight of isooctyl acrylate, add 0.01 part by weight of dibutyltin dilaurate dropwise, add 2.25 parts by weight of isophorone diisocyanate and mix, react at 20°C for 1 hour, add 0.6 parts by weight of hydroxyethyl acrylate and carry out end-capping reaction at 40°C for 6 hours until the isocyanate group is completely reacted, thereby obtaining the polyurethane acrylate oligomer A-1.
[0055] Preparation Example 2
[0056] This preparation example provides a polyurethane acrylate oligomer A, specifically a polyurethane acrylate oligomer A-2, and the polyurethane acrylate oligomer A-2 is prepared by the following method:
[0057] (1) Dissolve 1 part by weight of 5,7-dihydroxy-4-methylcoumarin in 18 parts by weight of dimethylformamide, add 7 parts by weight of potassium carbonate, dropwise add 2.5 parts by weight of 4-bromo-1-butanol, react at 90° C. for 16 hours, separate and purify to obtain a compound having a structure as shown in Formula I-1;
[0058]
[0059] (2) Dissolve 1 part by weight of the compound having the structure shown in Formula I-1 obtained in step (1) in 1 part by weight of isooctyl acrylate, add 0.005 parts by weight of dibutyltin dilaurate dropwise, add 2.28 parts by weight of isophorone diisocyanate and mix, react at 40° C. for 0.5 h, add 1.6 parts by weight of caprolactone acrylate and carry out end-capping reaction at 40° C. for 6 h until the isocyanate group is completely reacted, thereby obtaining the polyurethane acrylate oligomer A-2.
[0060] Preparation Example 3
[0061] This preparation example provides a polyurethane acrylate oligomer A, specifically a polyurethane acrylate oligomer A-3, and the polyurethane acrylate oligomer A-3 is prepared by the following method:
[0062] (1) Dissolve 1 part by weight of 5,7-dihydroxy-4-methylcoumarin in 22 parts by weight of dimethylformamide, add 8 parts by weight of potassium carbonate, dropwise add 2.26 parts by weight of 2-bromoethanol, react at 80° C. for 20 hours, separate and purify to obtain a compound having a structure as shown in Formula I-2;
[0063]
[0064] (2) Dissolve 1 part by weight of the compound having the structure shown in Formula I-2 obtained in step (1) in 1 part by weight of isooctyl acrylate, add 0.008 part by weight of dibutyltin dilaurate dropwise, add 2.28 parts by weight of isophorone diisocyanate and mix, react at 40°C for 0.5h, add 0.6 part by weight of hydroxyethyl acrylate and carry out end-capping reaction at 60°C for 4h until the isocyanate group is completely reacted, thereby obtaining the polyurethane acrylate oligomer A-3.
[0065] Example 1
[0066] The present embodiment provides a reworkable UV-curable adhesive and a preparation method thereof, wherein the reworkable UV-curable adhesive comprises the following components in percentage by mass: 35% of acrylate monomers (composed of 28% of isobornyl acrylate and 12% of tetrahydrofuran acrylate), 28% of polyurethane acrylate oligomer A (polyurethane acrylate oligomer A-1 provided in Preparation Example 1), 25% of polyurethane acrylate oligomer B (CN8888, Sartomer Company), 4% of a photoinitiator (1-hydroxycyclohexyl phenyl ketone and phenyl bis(2,4,6-trimethylbenzoyl)phosphine oxide in a mass ratio of 3:1), and 3% of a filler (hydrophobic fumed silica Aerosil R202).
[0067] The preparation method comprises the following steps: mixing acrylate monomers, polyurethane acrylate oligomer A and polyurethane acrylate oligomer B, then adding a photoinitiator and a filler, stirring and mixing until the mixture is stirred evenly without insoluble particles, thereby obtaining the reworkable UV curing adhesive.
[0068] Example 2
[0069] The present embodiment provides a reworkable UV-curable adhesive and a preparation method thereof, which differs from the embodiment 1 only in that the reworkable UV-curable adhesive comprises the following components by mass percentage: 35% of acrylate monomer (composed of 17% of isobornyl acrylate, 8% of N,N-methylacrylamide and 10% of ethoxylated tetrahydrofuran acrylate), 21% of polyurethane acrylate oligomer A (polyurethane acrylate oligomer A-2 provided in Preparation Example 2), 35% of polyurethane acrylate oligomer B (BR-543M, Bomar Company), 5% of photoinitiator (1-hydroxycyclohexyl phenyl ketone and phenyl bis(2,4,6-trimethylbenzoyl)phosphine oxide in a mass ratio of 3:1) and 4% of filler (hydrophobic fumed silica Aerosil R202), and other conditions are the same as those in the embodiment 1.
[0070] Example 3
[0071] The present embodiment provides a reworkable UV-curable adhesive and a preparation method thereof, which differs from Example 1 only in that the reworkable UV-curable adhesive comprises the following components by mass percentage: 39% of acrylate monomers (composed of 21% of isobornyl acrylate, 8% of N,N-methylacrylamide and 10% of acetone glycerol acrylate), 30% of polyurethane acrylate oligomer A (polyurethane acrylate oligomer A-1 provided in Preparation Example 1), 22% of polyurethane acrylate oligomer B (CN8888, Sartomer Company), 5% of photoinitiator (1-hydroxycyclohexyl phenyl ketone and phenyl bis(2,4,6-trimethylbenzoyl)phosphine oxide in a mass ratio of 3:1) and 4% of filler (hydrophobic fumed silica Aerosil R202), and other conditions are the same as those in Example 1.
[0072] Example 4
[0073] The present embodiment provides a reworkable UV-curable adhesive and a preparation method thereof, which differs from Example 1 only in that the reworkable UV-curable adhesive comprises the following components by mass percentage: 48% of acrylate monomers (composed of 20% of trimethylolcyclohexyl acrylate, 8% of N,N-methylacrylamide and 20% of acetone glycerol acrylate), 18% of polyurethane acrylate oligomer A (polyurethane acrylate oligomer A-1 provided in Preparation Example 1), 31% of polyurethane acrylate oligomer B (CN8888, Sartomer Company), 2% of photoinitiator (1-hydroxycyclohexyl phenyl ketone and phenyl bis(2,4,6-trimethylbenzoyl)phosphine oxide in a mass ratio of 3:1) and 1% of filler (hydrophobic fumed silica Aerosil R202), and other conditions are the same as those in Example 1.
[0074] Example 5
[0075] This embodiment provides a reworkable UV-curable adhesive and a preparation method thereof, which differs from Example 1 only in that the mass percentage of polyurethane acrylate oligomer A (polyurethane acrylate oligomer A-1 provided in Preparation Example 1) is adjusted to 35%, and the mass percentages of other components are reduced proportionally, a total reduction of 7%, and other conditions are the same as in Example 1.
[0076] Example 6
[0077] This embodiment provides a reworkable UV-curable adhesive and a preparation method thereof, which differs from Example 1 only in that 1-hydroxycyclohexyl phenyl ketone and phenyl bis(2,4,6-trimethylbenzoyl)phosphine oxide in a mass ratio of 3:1 are replaced with 1-hydroxycyclohexyl phenyl ketone of the same mass, and other conditions are the same as those in Example 1.
[0078] Example 7
[0079] This embodiment provides a reworkable UV-curable adhesive and a preparation method thereof, which differs from Embodiment 1 only in that 1-hydroxycyclohexyl phenyl ketone and phenyl bis(2,4,6-trimethylbenzoyl)phosphine oxide in a mass ratio of 3:1 are replaced with phenyl bis(2,4,6-trimethylbenzoyl)phosphine oxide of the same mass, and other conditions are the same as those in Embodiment 1.
[0080] Example 8
[0081] This embodiment provides a reworkable UV-curable adhesive and a preparation method thereof, which differs from Embodiment 1 only in that 1-hydroxycyclohexyl phenyl ketone and phenyl bis(2,4,6-trimethylbenzoyl)phosphine oxide in a mass ratio of 3:1 are replaced with 2-isopropylthioxanthone of the same mass, and other conditions are the same as those in Embodiment 1.
[0082] Example 9
[0083] This embodiment provides a reworkable UV-curable adhesive and a preparation method thereof, which differs from Example 1 only in that the polyurethane acrylate oligomer A-1 provided in Preparation Example 1 is replaced with the polyurethane acrylate oligomer A-3 provided in Preparation Example 3 of the same mass, and other conditions are the same as in Example 1.
[0084] Example 10
[0085] This embodiment provides a reworkable UV-curable adhesive and a preparation method thereof, which differs from Example 1 only in that the mass percentage of polyurethane acrylate oligomer A (polyurethane acrylate oligomer A-1 provided in Preparation Example 1) is adjusted to 15%, and the mass percentages of other components are increased proportionally, a total increase of 13%, and other conditions are the same as in Example 1.
[0086] Embodiment 11
[0087] This embodiment provides a reworkable UV-curable adhesive and a preparation method thereof, which differs from Example 1 only in that the mass percentage of polyurethane acrylate oligomer A (polyurethane acrylate oligomer A-1 provided in Preparation Example 1) is adjusted to 38%, and the mass percentages of other components are reduced proportionally, a total reduction of 10%, and other conditions are the same as in Example 1.
[0088] Example 12
[0089] This embodiment provides a reworkable UV-curable adhesive and a preparation method thereof, which is different from Embodiment 1 only in that the mass percentage of the photoinitiator (1-hydroxycyclohexyl phenyl ketone and phenyl bis(2,4,6-trimethylbenzoyl)phosphine oxide in a mass ratio of 3:1) is adjusted to 1%, and the mass percentages of other components are increased proportionally, a total increase of 3%, and other conditions are the same as in Embodiment 1.
[0090] Example 13
[0091] This embodiment provides a reworkable UV-curable adhesive and a preparation method thereof. The only difference between this embodiment and Embodiment 1 is that the mass percentage of polyurethane acrylate oligomer B (CN8888, Sartomer Company) is adjusted to 18%, and the mass percentages of other components are increased proportionally, a total increase of 7%. Other conditions are the same as in Embodiment 1.
[0092] Embodiment 14
[0093] This embodiment provides a reworkable UV-curable adhesive and a preparation method thereof. The only difference between this embodiment and Embodiment 1 is that the mass percentage of polyurethane acrylate oligomer B (CN8888, Sartomer Company) is adjusted to 38%, and the mass percentages of other components are reduced proportionally, a total reduction of 13%. Other conditions are the same as in Embodiment 1.
[0094] Comparative Example 1
[0095] This comparative example provides a photocurable adhesive and a preparation method thereof, which differs from Example 1 only in that polyurethane acrylate oligomer A is not added, the mass percentages of other components are increased proportionally, and a total increase of 28%, and other conditions are the same as Example 1.
[0096] The reworkable UV-curable adhesives provided in the above-mentioned Examples 1-14 and the light-curable adhesive provided in Comparative Example 1 were tested, and the specific testing methods are as follows.
[0097] The reworkable UV-curable adhesive or photo-curable adhesive to be tested is applied between a polycarbonate (PC) sheet and an acrylonitrile-butadiene-styrene copolymer (ABS) sheet and irradiated with 350nm UV light for 10s with an energy of 5000mJ / cm 2 , get the test sample.
[0098] Initial bonding strength: The above test samples were tested in accordance with GB / T 7124-2008 to obtain the initial bonding strength;
[0099] Repairability: The adhesive layer of the above test sample was irradiated with 254nm ultraviolet light for 120s, with an energy of 60000mJ / cm 2 , forming a softened adhesive layer, and obtaining the first bonding strength according to GB / T 7124-2008 test; finally, irradiate the softened adhesive layer with 350nm ultraviolet light for 10s, with an energy of 5000mJ / cm 2 , the second bonding strength was obtained according to the GB / T7124-2008 test.
[0100] The test results are shown in Table 1 below:
[0101] Table 1
[0102]
[0103]
[0104] It can be seen from the contents of Table 1 that the initial bonding strength of the reworkable UV-curable adhesive provided in Examples 1-14 after curing with 350nm UV light is ≥4MPa, the bonding strength is reduced to ≤3MPa after 254nm UV light irradiation, and the bonding strength can be restored to ≥2MPa after 350nm UV light irradiation.
[0105] Compared with Example 1, if the combination of 1-hydroxycyclohexyl phenyl ketone and phenyl bis (2,4,6-trimethylbenzoyl) phosphine oxide is replaced with 1-hydroxycyclohexyl phenyl ketone (Example 6) or phenyl bis (2,4,6-trimethylbenzoyl) phosphine oxide (Example 7) of the same mass, the photoinitiator initiation efficiency is low, resulting in low conversion rate of acrylate double bonds in the repairable UV-curable adhesive after 350nm UV irradiation, incomplete curing, and low initial bonding strength. It can be seen that the performance of the repairable UV-curable adhesive prepared by the combination of 1-hydroxycyclohexyl phenyl ketone and phenyl bis (2,4,6-trimethylbenzoyl) phosphine oxide in the present invention is better.
[0106] Compared with Example 1, if the mass percentage of polyurethane acrylate oligomer A is too low (Example 10), the initial bonding strength of the repairable UV-curable adhesive is low, and after subsequent crosslinking under 254nm UV irradiation, the bonding strength is still high, which is not conducive to repair; if the mass percentage of polyurethane acrylate oligomer A is too high (Example 11), the crosslinking density of the repairable UV-curable adhesive is too high under 350nm light source irradiation, the shrinkage is too large, and the strength of the colloid body after curing is too high, so that the initial bonding strength is relatively low, and the bonding effect on polycarbonate sheets and acrylonitrile-styrene-butadiene copolymer sheets is poor. It can be seen that the performance of the repairable UV-curable adhesive prepared with the mass percentage of polyurethane acrylate oligomer A within a specific range is better.
[0107] Compared with Example 1, if the mass percentage of the photoinitiator is too low (Example 12), the repairable UV-curable adhesive has a low crosslinking density and a low initial bonding strength under 350nm curing.
[0108] Compared with Example 1, if the mass percentage of polyurethane acrylate oligomer B is too high (Example 14), after curing and irradiation at 254nm to decrosslink, the acrylate crosslinking density is still very large, the bonding strength is high, and subsequent rework and repair are difficult. If the mass percentage of polyurethane acrylate oligomer B is too low (Example 13), the initial bonding strength of the reworkable UV-curable adhesive after irradiation with 350nm UV light is low, which is difficult to meet daily bonding applications.
[0109] Compared with Example 1, if the polyurethane acrylate oligomer A is not added (Comparative Example 1), the photocurable adhesive cannot be de-crosslinked after curing, and rework cannot be performed.
[0110] The applicant declares that the present invention uses the above-mentioned embodiments to illustrate a reworkable UV curing adhesive and its preparation method and rework method, but the present invention is not limited to the above-mentioned embodiments, that is, it does not mean that the present invention must rely on the above-mentioned embodiments to be implemented. Those skilled in the art should understand that any improvement of the present invention, equivalent replacement of various raw materials of the product of the present invention, addition of auxiliary components, selection of specific methods, etc., all fall within the protection scope and disclosure scope of the present invention.
Claims
1. A reworkable UV curing adhesive, It is characterized in that The reworkable UV curable adhesive comprises the following components: acrylate monomers, polyurethane acrylate oligomer A, polyurethane acrylate oligomer B, photoinitiator and filler; The raw materials for preparing the polyurethane acrylate oligomer A include 5,7-dihydroxy-4-methylcoumarin, halogen-substituted monoalkyl alcohol, isooctyl acrylate, isophorone diisocyanate and a hydroxyl-containing acrylate compound.
2. The reworkable UV curing adhesive according to claim 1, It is characterized in that The acrylic ester monomers include any one or a combination of at least two of isobornyl acrylate, N,N-dimethylacrylamide, hydroxyethyl methacrylate, tetrahydrofuran acrylate, tetrahydrofuran methacrylate, ethoxylated tetrahydrofuran acrylate, trimethylolcyclohexyl acrylate, acetone glycerol acrylate or cyclotrimethylolpropane formal acrylate.
3. The reworkable UV curing adhesive according to claim 1 or 2, It is characterized in that The halogen-substituted monohydric alkyl alcohol includes chlorine-substituted monohydric alkyl alcohol and / or bromine-substituted monohydric alkyl alcohol; Preferably, the halogen-substituted monohydric alkyl alcohol comprises 4-bromo-1-butanol and / or 2-bromoethanol; Preferably, the hydroxyl-containing acrylate compound includes any one or a combination of at least two of hydroxyethyl acrylate, hydroxyethyl methacrylate, hydroxypropyl acrylate, hydroxybutyl acrylate or caprolactone acrylate; Preferably, the polyurethane acrylate oligomer A is prepared by the following method: (1) reacting 5,7-dihydroxy-4-methylcoumarin with a halogen-substituted monoalkyl alcohol to obtain a compound having a structure as shown in Formula I; In formula Ⅰ, R is an alkylene group having 2 to 10 carbon atoms; (2) The compound having the structure shown in Formula I obtained in step (1) is dissolved in isooctyl acrylate, and then mixed with isophorone diisocyanate, reacted, and a hydroxyl-containing acrylate compound is added for end-capping reaction to obtain the polyurethane acrylate oligomer A.
4. The reworkable UV curing adhesive according to claim 3, It is characterized in that The mass ratio of the 5,7-dihydroxy-4-methylcoumarin and the halogen-substituted monoalkyl alcohol in step (1) is 1:(2-2.5); Preferably, the mass ratio of the compound having the structure shown in formula I to isophorone diisocyanate in step (2) is 1:(2-3); Preferably, the mass ratio of the compound having the structure shown in formula I to isooctyl acrylate in step (2) is 1:(0.8-1.2); Preferably, the mass ratio of isophorone diisocyanate to the hydroxyl-containing acrylate compound in step (2) is 1:(0.6-1.9); Preferably, the reaction temperature in step (1) is 80-90°C and the reaction time is 16-20h; Preferably, the reaction temperature in step (2) is 20-40° C. and the reaction time is 0.5-1 h; Preferably, the temperature of the end-capping reaction in step (2) is 40-60° C. and the time is 4-6 hours.
5. The reworkable UV curing adhesive according to claim 3 or 4, It is characterized in that The step (1) specifically comprises the following steps: dissolving 5,7-dihydroxy-4-methylcoumarin in a solvent, adding potassium carbonate, dropping a halogen-substituted monoalkyl alcohol, reacting at 80 to 90° C. for 16 to 20 hours, separating and purifying to obtain a compound having a structure as shown in Formula I-1; Preferably, the solvent in step (1) comprises dimethylformamide; Preferably, the mass ratio of the 5,7-dihydroxy-4-methylcoumarin to the solvent in step (1) is 1:(18-22); Preferably, the mass ratio of 5,7-dihydroxy-4-methylcoumarin to potassium carbonate in step (1) is 1:(7-10).
6. The reworkable UV curing adhesive according to any one of claims 3 to 5, It is characterized in that The step (2) specifically comprises the following steps: dissolving the compound having the structure shown in formula I in isooctyl acrylate, mixing with a catalyst and isophorone diisocyanate, reacting at 20 to 40° C. for 0.5 to 1 h, adding a hydroxyl-containing acrylate compound and performing a capping reaction at 40 to 60° C. for 4 to 6 h to obtain the polyurethane acrylate oligomer A; Preferably, the catalyst in step (2) comprises dibutyltin dilaurate; Preferably, the mass ratio of the compound having the structure shown in formula I to the catalyst in step (2) is 1:(0.005-0.01).
7. The reworkable UV curing adhesive according to any one of claims 1 to 6, It is characterized in that The photoinitiator includes any one or a combination of at least two of 1-hydroxycyclohexyl phenyl ketone, 2,4,6-(trimethylbenzoyl)diphenyl phosphine oxide, 2-methyl-1-(4-methylthiophenyl)-2-morpholinyl-1-propanone, 2-hydroxy-2-methyl-1-phenyl-1-propanone, 2-phenylbenzyl-2-dimethylamine-1-(4-morpholinobenzylphenyl)butanone, methyl benzoylformate, phenylbis(2,4,6-trimethylbenzoyl)phosphine oxide, 2-isopropylthioxanthone, benzoin dimethyl ether, dimethylbenzil ketal or benzophenone, and more preferably a combination of 1-hydroxycyclohexyl phenyl ketone and phenylbis(2,4,6-trimethylbenzoyl)phosphine oxide; Preferably, the filler comprises hydrophobic fumed silica; Preferably, the reworkable UV-curable adhesive comprises the following components by mass percentage: 35% to 48% of acrylate monomer, 18% to 35% of polyurethane acrylate oligomer A, 20% to 35% of polyurethane acrylate oligomer B, 2% to 5% of photoinitiator and 1% to 4% of filler.
8. A method for preparing the reworkable UV curing adhesive according to any one of claims 1 to 7, It is characterized in that The preparation method comprises mixing acrylate monomers, polyurethane acrylate oligomer A, polyurethane acrylate oligomer B, a photoinitiator and a filler to obtain the reworkable ultraviolet light curing adhesive.
9. The preparation method according to claim 8, It is characterized in that The mixing specifically includes mixing acrylate monomers, polyurethane acrylate oligomer A, and polyurethane acrylate oligomer B, and then adding a photoinitiator and a filler and stirring and mixing.
10. A method for repairing a repairable UV curing adhesive as claimed in any one of claims 1 to 7, It is characterized in that The repair method comprises the following steps: irradiating the cured repairable UV curing adhesive as described in any one of claims 1 to 7 with 254nm UV light, healing micro cracks or macro damage by heating or high frequency vibration, and then irradiating with 350nm UV light to complete the repair.
